Sink electrical discharge machining of hydrophobic surfaces - Guo, Changcheng; Koshy, Philip; Coelho, Felipe [UNESP]; Selvaganapathy, P. Ravi (Elsevier B.V., 2019)
The phenomenon of hydrophobicity observed in such surfaces as lotus leaves is typically manifest by hierarchical structures on low-energy surfaces. Sustained interest in fabricating hydrophobic surfaces has resulted in a myriad of processes, which are but limited by their largely referring to soft materials and/or involving multiple process steps. The present work explored the application of electrical discharge machining (EDM) for the single-step manufacture of durable, metallic hydrophobic surfaces. Simple sink EDM in a hydrocarbon dielectric, with no special process kinematic or tooling requirements, is demonstrated to rapidly generate surfaces that are intrinsically water repellent, with contact angles approaching 150 degrees. (C) 2019 Published by Elsevier Ltd on behalf of CIRP.
Keywords: Material removal; Texture; Topography